The influence of competence, motivation, and work culture on employee performance through self-efficacy as an intervening variable for medical support employees Regional General Hospital Tanjungpinang City - Muliyanto Muliyanto; Indrayani Indrayani; Bambang Satriawan; Ngaliman Ngaliman; I Wayan Catrayasa (Goodwood Publishing, 2023)
Purpose: This study investigates the impact of competence, motivation, and work culture on employee performance, with self-efficacy as the mediating variable. It hypothesizes that competence, motivation, and work culture influence self-efficacy, which in turn affects performance. Research Methodology: The sample in this study included all Medical Support employees at the Tanjungpinang City Regional General Hospital. The number of samples used was 105. The data obtained were analyzed using data analysis techniques with AMOS 24.0 software. Results: The findings revealed the significance of these relationships: competence positively affected self-efficacy, as indicated by the CR Value (5.045) and probability (0.000 < 0.05). Similarly, motivation (CR Value 2.802, P-Value 0.002 < 0.05) and work culture (CR Value 4.267, P-Value 0.001 < 0.05) positively impacted self-efficacy. Competence (CR = 3.066, p = 0.002 < 0.05) and work culture (CR = 2.075, p = 0.039 < 0.05) significantly influenced performance through self-efficacy. However, motivation does not have a direct significant effect on performance (CR Value = 1.157, probability = 0.248 > 0.05). Conclusions: Competence and work culture enhance performance through self-efficacy, while motivation indirectly supports it by strengthening self-efficacy. Limitations: This research focuses on 105 Medical Support employees at the Tanjungpinang City Regional General Hospital, employing AMOS 24.0 for data analysis. Contribution: This study underscores the importance of competence, motivation, and work culture in enhancing employee performance through the mediating role of self-efficacy.